PENERAPAN HEALTH BELIEF MODEL SEBAGAI UPAYA PENCEGAHAN INFEKSI MENULAR SEKSUAL PADA IBU RUMAH TANGGA - Silvia Ari Agustina; Bhisma Murti; Argyo Demartoto (MEDIA ILMU KESEHATAN, 2016)
Background: Sexual and reproductive health issues are increasingly of concern world wide among other circumstances related to genital hygiene. Poor genital hygiene will increase the risk of Sexually Transmitted Infections (STIs). Health Belief Model (HBM) is a set of self-perceptions that determines the health behavior of an individual. Objective: This study aimed to analyze the application of the health belief model with genital hygiene practice of housewives in Cangkringan. Method: This study employed mixed-methods with sequential explanatories strategy and cross sectional design. A total of 101 housewives, including 2 housewives, 2 husbands, officers of clinics that serve STIs screening and 1 non-governmental organization were recruited using quota sampling. Data were collected with a questionnaire, interviews and were analyzed using linear regression. Triangulation was conducted to achieve validity and reliability. Results: Genital hygiene had a positive relationship with the perception of vulnerability (b:0.97; 95% CI: 0.87 to 1.06; p < 0.01), self-efficacy (b: 0.02; CI 95%: 0.00 to 0.05; p 0.05), and cues to genital hygiene action (b:0,16; 95% CI: 0.08 up to 0.23; p < 0.01). There was a negative relationship between genital hygiene with the perception of hygiene barriers (b:-0.13; 95% CI:-0.18 to 0.09-; p < 0.01). The linear regression model showed that independent variables altogether contribute to 84.5% of genital hygiene. Housewives stated that genital hygiene was important, but maintained inappropriate practices, such as frequently use of femininity cleanser, wearing tight underwears, and using pentyliner. Conclusion: There are four components of Health Belief Model associated with genital hygiene. Keywords: Health belief model, genital hygiene